Transformasi Manajemen Pendidikan Islam Melalui Perencanaan Adaptif di Era Digital. - Rohaniyah, Aisyah; Mardiyah, Mardiyah (Jurnal Administrasi Pendidikan Islam, 2024)
Educational planning is often treated as a linear administrative activity ending in a formal document, an approach inadequate amid digital transformation, artificial intelligence, and recurring disruptions. This article aims to reconstruct educational planning within Islamic educational management as an adaptive, evidence informed, participatory, and value based cycle. Employing an integrative literature review, the study analyzed academic books, peer reviewed articles, and institutional reports through thematic reduction and synthesis. The findings reveal that effective planning must combine six principles, namely clear direction, evidence use, stakeholder participation, resource alignment, ethical equity safeguards, and iterative adjustment. Consequently, this study proposes a 6D framework, Diagnosis, Direction, Design, Deployment, Data Review, and Dynamic Adjustment, strengthened by Islamic values of amanah, shura, justice, and public benefit. This framework offers a contemporary conceptual synthesis and practical architecture for madrasahs, pesantren, and Islamic higher education institutions to translate vision into revisable action.